2020
DOI: 10.26434/chemrxiv.12362333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Compounds as Inhibitors of SARS-CoV-2 Main Protease (3CLpro): A Molecular Docking and Simulation Approach to Combat COVID-19

Abstract: <p></p><p>Recently, the emergence and dissemination of SARS-CoV-2 has caused high mortality and enormous economic loss. In the fight against COVID-19, the rapid development of new drug molecules is the need of hour. However, the conventional approaches of drug development is time consuming and expensive in nature. In this study, we have adopted an alternative approach to identify lead molecules from natural sources using high throughput virtual screening approach. Ligands from natural compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Moreover, a molecular docking study revealed that Kaempferol might also act on SARS‐CoV‐2 3CL pro , showing binding energy and binding affinity of −7.8 kcal/mol and 5.2 × 10 5 M −1 , respectively. It forms two hydrogen bonds, in which the one with the Gln189 residue described previously is critical to the catalytic activity of 3CL pro (Rehman et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, a molecular docking study revealed that Kaempferol might also act on SARS‐CoV‐2 3CL pro , showing binding energy and binding affinity of −7.8 kcal/mol and 5.2 × 10 5 M −1 , respectively. It forms two hydrogen bonds, in which the one with the Gln189 residue described previously is critical to the catalytic activity of 3CL pro (Rehman et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…Because SARS‐CoV‐2 3CL pro maintains the same residue Gln189 in its active site, it is suggested that the main protease of the novel coronavirus may also be sensitive to the inhibitory action of quercetin and its derivatives. Importantly, a recent computational study revealed that quercetin is predicted to form a hydrogen bond with Gln186 on active site of SARS‐CoV‐2 3CL pro , which results in low binding energy (−7.5 kcal/mol) and consequent high binding affinity (3.2 × 10 5 M −1 ) (Rehman, AlAjmi, & Hussain, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is also a well-known fact that their adequate intake may help to modulate immune responses and resistance to infection. The efficacy of polyphenols as antiviral compounds has been frequently reported, and there is an enormous potential in exploring their antiviral properties, since they are commonly recognized as safe and effective in substituting for, or in serving as an adjunct treatment to, conventional therapies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Although, there is already substantial information about polyphenols' activity against SARS-CoV-2, most of these results are derived from computational modeling and computational predictions, and their capability as anti-SARS-CoV-2 agents still needs to be scientifically and clinically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Some active ingredients found in Yinqiao powder by high‐performance liquid chromatography analysis may have anti‐COVID‐19 effects, such as rutin and hesperidin (Shu et al, 2012). Rehman, AlAjmi, and Hussain (2020) and Liang et al (2020) found that the binding affinity of rutin for the main protease (3CL pro ) of SARS‐CoV‐2 was much higher than that of chloroquine, hydroxychloroquine, and remdesivir, and it may inhibit COVID‐19 by downregulating IL‐6. Balmeh et al found that hesperidin has an inhibitory effect on human angiotensin‐converting enzyme 2 (ACE2), TMPRSS2, GRP78, and AT1R receptors and may have the ability to treat COVID‐19 infection (Balmeh, Mahmoudi, Mohammadi, & Karabedianhajiabadi, 2020).…”
Section: Introductionmentioning
confidence: 99%